2000
DOI: 10.1046/j.1365-2648.2000.t01-1-01555.x
|View full text |Cite
|
Sign up to set email alerts
|

Women with learning disabilities: risk behaviours and experiences of the cervical smear test

Abstract: This paper reports the findings of a study on the views and experiences of women with learning disabilities regarding the cervical smear test. The experience and opinions of the carers were also taken into account. The study was carried out between 1997 and 1999 in Cambridgeshire. The factors that influenced whether women with a learning disability had a smear test included: sexual activity; number of sexual partners; pregnancy; and a past history of smoking. Women with a learning disability who had a cervical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…The majority of the women (17) expressed a preference for seeing a woman doctor when it came to matters relating to contraception (see also McCarthy 2002; Broughton & Thomson 2000). Most women felt this way because it was simply more comfortable for them to talk to another woman (‘I’d be embarrassed with a man’), but for some women it was that they felt vulnerable with male doctors (‘I have to have a lady doctor.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the women (17) expressed a preference for seeing a woman doctor when it came to matters relating to contraception (see also McCarthy 2002; Broughton & Thomson 2000). Most women felt this way because it was simply more comfortable for them to talk to another woman (‘I’d be embarrassed with a man’), but for some women it was that they felt vulnerable with male doctors (‘I have to have a lady doctor.…”
Section: Resultsmentioning
confidence: 99%
“…These authors make the telling comment that is was not possible to predict which women had been sexually active, a significant point given the assumption that because a woman has intellectual disabilities, she is therefore unlikely to be sexually active. Broughton & Thomson (2000) report that women who have had the cervical smear test experience pain and find the procedure a difficult one. They note the importance of extended preparation for examination, of good communication and provision of information and the key role of carers.…”
Section: Resultsmentioning
confidence: 99%
“…The results provide the vital information to the further health policy initiation to increase the screening rate of this vulnerable population. Other studies also found many factors to affect the Pap smear screening in women with ID, such as Broughton and Thomson (2000) found the factors that influenced whether women with ID had a smear test included: sexual activity; number of sexual partners; pregnancy; and a past history of smoking.…”
Section: Reynolds Stanistreet and Eltonmentioning
confidence: 99%